CLINICAL MANIFESTATION AND PATHOGENESIS OF NERVOUS SYSTEM INVOLVEMENT IN SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS-2 INFECTION - DEWI, VALENTINA TJANDRA; LAKSMIDEWI, ANAK AGUNG AYU PUTRI; AYU SUDIARIANI, KETUT (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) or CoV disease 2019 (COVID-19) infection has spread throughout the world and becomes a global pandemic. Various studies are still ongoing to be able to understand this viral infection in terms of symptomatology, transmission, pathogenesis, its treatment, and prevention. In addition to respiratory symptoms that are commonly reported in SARS-CoV-2 infections, there are many reports of symptoms appearing in other organ systems with one of them being neurological manifestation. The neurological manifestations involve not only the central and peripheral nervous systems but also there was also a suspicion that the potential invasion of SARS-CoV-2 in the nervous system might be able to take part in the occurrence of respiratory failure that is found in patients with COVID-19. The continuity of the study and the awareness of medical personnel from various fields of science must be increased to fight against the COVID-19 pandemic and ensuring optimal treatment for patients.